2008 IEEE Congress on Evolutionary Computation (IEEE World Congress on Computational Intelligence) 2008
DOI: 10.1109/cec.2008.4631079
|View full text |Cite
|
Sign up to set email alerts
|

Application of Memetic Differential Evolution frameworks to PMSM drive design

Abstract: This paper proposes the application of Memetic Algorithms employing Differential Evolution as an evolutionary framework in order to achieve optimal design of the control system for a permanent-magnet synchronous motor. Two Memetic Differential Evolution frameworks have been considered in this paper and their performance has been compared to a standard Differential Evolution, a standard Genetic Algorithm and a Memetic Algorithm presented in literature for solving the same problem. All the algorithms have been t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Memetic Algorithm (MA) represents a subfield of Memetic Computing (MC) (Ong, Lim, and Chen 2010) that is widely established as the synergy of populationbased approaches with separate lifetime learning (a.k.a., local search or individual learning) process. Recent studies on MAs have shown that they can converge to high-quality solutions more efficiently than their conventional counterparts on a wide range of domains covering problems in combinatorial (Lim and Xu 2005;Tang, Lim, Ong, and Er 2006;Lim, Ong, Lim, Chen, and Agarwal 2008;Hasan, Sarker, Essam, and Cornforth 2009;Meuth, Wunsch, Saad, and Vian 2010), continuous (Aranha and Iba 2009;Chiam, Tan, and Mamun 2009;Kramer 2010;Neri and Mininno 2010), dynamic (Lim, Ong, and Lee 2005;Goh and Tan 2007;Caponio, Neri, Cascella, and Salvatore 2008) and multi-objective optimisations (Ishibuchi, Yoshida, and Murata 2002;Tan, Khor, and Lee 2005;Goh, Ong, and Tan 2009) Algorithm 1 outlines the schematic workflow of a canonical MA. The algorithm starts with the initialisation of a population Pop(gen ¼ 0) of candidate solutions.…”
Section: Safety Stock For Managerial Control Over Route Failure In Vrpsdmentioning
confidence: 98%
“…Memetic Algorithm (MA) represents a subfield of Memetic Computing (MC) (Ong, Lim, and Chen 2010) that is widely established as the synergy of populationbased approaches with separate lifetime learning (a.k.a., local search or individual learning) process. Recent studies on MAs have shown that they can converge to high-quality solutions more efficiently than their conventional counterparts on a wide range of domains covering problems in combinatorial (Lim and Xu 2005;Tang, Lim, Ong, and Er 2006;Lim, Ong, Lim, Chen, and Agarwal 2008;Hasan, Sarker, Essam, and Cornforth 2009;Meuth, Wunsch, Saad, and Vian 2010), continuous (Aranha and Iba 2009;Chiam, Tan, and Mamun 2009;Kramer 2010;Neri and Mininno 2010), dynamic (Lim, Ong, and Lee 2005;Goh and Tan 2007;Caponio, Neri, Cascella, and Salvatore 2008) and multi-objective optimisations (Ishibuchi, Yoshida, and Murata 2002;Tan, Khor, and Lee 2005;Goh, Ong, and Tan 2009) Algorithm 1 outlines the schematic workflow of a canonical MA. The algorithm starts with the initialisation of a population Pop(gen ¼ 0) of candidate solutions.…”
Section: Safety Stock For Managerial Control Over Route Failure In Vrpsdmentioning
confidence: 98%
“…Mutation probability and other search parameters depend also on the diversity measure. the FAMA algorithm was compared against Tirronen's algorithm and SFMDE obtaining better results for the problem of permanent magnet synchronous motors [13].…”
Section: Preliminariesmentioning
confidence: 99%
“…FAMA includes a self-adaptive criterium based on a fitness diversity measure and the iteration number. Mutation probability and other search parameters depend also on the diversity measure, the FAMA algorithm was compared against Tirronen's algorithm and SFMDE obtaining better results for the problem of permanent magnet synchronous motors (Caponio et al 2008). …”
Section: Related Workmentioning
confidence: 99%